Effects of TNF antagonists on sperm characteristics in patients with spondyloarthritis. Issue 10 (7th July 2010) - Villiger, Peter M; Caliezi, Gion; Cottin, Véronique; Förger, Frauke; Senn, Alfred; Østensen, Monika
Abstract : Objective: To study the influence of tumour necrosis factor (TNF) antagonists on spermatogenesis in a cohort of patients with spondyloarthritis (SpA). Patients and methods: Semen samples of 26 patients with SpA were analysed according to WHO 1999 guidelines with and without TNF blocking agents (infliximab, etanercept or adalimumab). Results were compared with semen samples of 102 healthy volunteers. Results: Sperm abnormalities were found in 10/11 patients without anti-TNF therapy. The sperm of these 11 patients had significantly poorer motility (p=0.001) and vitality (p=0.001) than found in 15 patients tested during longstanding anti-TNF therapy, but sperm concentration and morphology were similar in the two groups. There was no significant difference of sperm quality between healthy controls and anti-TNF treated patients with SpA. Notably, sperm abnormalities were also found in 102 healthy controls. Conclusion: Sperm abnormalities are a common finding in healthy men, they are more pronounced in patients with active SpA. The sperm quality of patients with SpA with inactive disease receiving long-term TNF inhibition is comparable to that in healthy controls. The data support continuation of anti-TNF treatment when fatherhood is planned.